PENYIMPANGAN KEBIJAKAN PENGIRIMAN TKI KE LUAR NEGERI - Made Ngurah Demi Andayana (Journal of Management Small and Medium Enterprises (SMEs), 2019)
Prospective TKI (Overseas Indonesian Workforce) are always faced with two difficult choices, namely by using a legal way through the official government-protected institution or illegal way that is unclear responsibilities. Illegal delivery of TKW (Women Workers) doing by uncompleted documents dominantely caused by family economic difficulties and lack of poverty. Administratively the prospective Indonesian workers do not have a KTP (ID), KK (Family Structure card), the birth certificate and the average education is uncompleted elementary school studies. There are still many employers or tekong who come to recruit directly in the cities and districts of NTT. A lack of understanding of citizen and district communities about the process of placing labor abroad from the government. Lack of good cooperation and support between government agencies related in the field of overseas employment placement. The lack of socialization policy of the policymakers abroad to the bottom level is the cause of the rise of migrant workers to Malaysia. Prospective migrant workers are in the community, the nearest ruler is the village head (RT, RW), Kampung, village/Kelurahan, Kecamatan to district, which has an obligation to provide information to the community. Due to the policy of delivery of special migrant workers abroad is if successful positively impact in the field of economy, because it produces foreign exchange that can help the growth of national economy and for TKI and their families are improving welfare. Keywords : Illegal Overseas Workers Supplies